Wildfire governance in a tri-national frontier of southwestern Amazonia: Capacities and vulnerabilities. (15th February 2023) - Pismel, Gleiciane O.; Marchezini, Victor; Selaya, Galia; de Paula, Yara A.P.; Mendoza, Eddy; Anderson, Liana O.
Abstract: Amazonian wildfires are an increasing hazard to ecosystem services and the regional population. Wildfires can turn into transboundary disasters primarily due to the effects of smoke that cross boundaries, compromising human health, disrupting transport, and affecting the regional economy. Wildfires are an increasing hazard at the southwestern amazonian tri-national frontier, which is composed of M adre de Dios (Peru), A cre (Brazil), and P ando (Bolivia), known as the MAP region. The understanding of wildfire governance is key for disaster risk reduction strategies. This paper analyses the perceptions about vulnerabilities and capacities in the wildfire governance in the MAP region, looking at four axes: i) risk knowledge; ii) monitoring; iii) education and communication; and iv) disaster prevention and response. The online survey (conducted between 2020 and 2021) had 111 regional stakeholders (practitioners, policy makers, NGO representatives and scientists). Approximately 60% of the participants considered deforestation the main driver contributing to wildfires, followed by fire use in agricultural management (58%) and droughts (39%). The main vulnerabilities in governance were organizational and sociocultural. The organizational vulnerability was associated with reduced employees and limited financial resources. In terms of political capacities, participants indicated strong articulation involving academia and NGOs. We conclude that the MAP region exhibits multiple vulnerabilities, such as weak organizations, reduced dialogue between governments and society, advancement of the agricultural frontier and increasing climatic extremes. It is key to prioritize strengthening organizational capacities, community involvement in wildfire governance, and greater integration between organizations and institutions, including seeking to formalize informal cooperation networks. Highlights: Wildfires can become transboundary disasters. In southwestern Amazonia, organizational weaknesses are the main vulnerability in wildfire governance. Lack of human and financial resources, and political influence are the main sources of organizational vulnerability. Informal cooperation networks are essential to governance, especially when organizations lack human or financial resources.